Patrimoines de papier. Superposition des aires naturelles protégées et développement territorial dans l’île de Lanzarote (Canaries, Espagne) - Igor Babou (VertigO)
what are the social and environmental effects of the multiplication of nature protection measures in the same area? Based on the ethnographic study of a fragile island territory (Lanzarote Island, Canary Islands, Spain), the diversity of its protected natural areas, its UNESCO listings (biosphere reserve and geopark) and local regulatory frameworks, this article shows the limited influence of environmental protection measures on the territory in a context characterized by political corruption and the high economic stakes of tourism. The superposition of heritage labels, far from leading to functional redundancies, or to synergies in the direction of sustainable development, produces in this context closing and competitive effects between heritage structures. A "brand" approach sometimes takes precedence over ecological issues that are well rooted in the history of the island of Lanzarote, but which are being eroded because they are not supported.